Services for spondyloarthritis: a survey of patients and rheumatologists. (23rd February 2018) - Derakhshan, Mohammad H; Pathak, Himanshu; Cook, Debbie; Dickinson, Sally; Siebert, Stefan; Gaffney, Karl; ,
Abstract: Objectives: There have been significant advances in axial spondyloarthritis (axSpA), with implications for service delivery. We evaluated the state of axSpA rheumatology services and how people with axSpA perceive their care. Methods: An online patient survey was emailed to all members of the National Ankylosing Spondylitis Society and advertised widely via social media. Separately, a Web-based questionnaire about axSpA services was sent to rheumatologists at all 172 acute hospital trusts in the UK. Results: From the National Ankylosing Spondylitis Society survey, data for 1979 surveys (56% males) were available for analysis. The majority of respondents had longstanding disease and identified their diagnosis as AS, with only 44% aware of the term axSpA. Eighty-two per cent of respondents were currently attending a rheumatologist, with 43% on biologic agents. Satisfaction scores for rheumatology care were high. Respondents' concerns included access during disease flares and adverse effects of analgesics. From the rheumatology survey, the concept and terminology of axSpA was widely accepted by respondents (88%). The majority of centres had at least one rheumatologist with a specialist interest in axSpA (62%), dedicated axSpA clinics (58%) or a multidisciplinary team for axSpA (64%). BASDAI (99%), BASFI (74%) and BASMI (65%) were routinely performed. All centres had access to MRI scans, but scanning protocols varied and were often sub-optimal. Conclusion: Although overall satisfaction with rheumatology care was high, the results indicate significant unmet patient needs and discrepancies in service provision. This information will inform the development of quality standards for axSpA in order to improve quality and deliver equitable care for all patients.